An Empirical Investigation of the Impact of FDI, Export and Gross Domestic Savings on the Economic Growth in Bangladesh - Miah, Md Mamun; Majumder, Shapan Chandra (The Economics and Finance Letters, 2020)
Bangladesh is a developing country with a huge population. So it is necessary to ensure better economic performance of Bangladesh. The purpose of the paper is to empirically investigate the impact of FDI, export, and gross domestic savings on the economic growth of Bangladesh and also tries to show the impact of inflation, industry value-added, and population growth on economic growth. We conduct the research with data covering the year from 1972 to 2017. Autoregressive Distributed Lag Bound Testing (ARDL BT) and Error Correction Model (ECM) are applied. The result of the ARDL model shows that the coefficient of FDI is 0.05 indicating that if FDI rises 1% then growth of the GDP will rise 0.05%. The coefficient of one year lag FDI is negative but insignificant. Again 1% rise in exports leads 0.03% rise in growth. Gross domestic savings positively affect GDP growth but statistically not significant. Inflation negatively affects the economic growth of Bangladesh. If inflation decreases by 1% then GDP growth will increase by 0.04%. Industry value added has positive effects on growth, a 1% increase in Industry value-added leads to a significant increasing in growth by 8.68%. Population growth negatively impacts economic growth. If the growth of the population decreases by 1% then 1.88% will increase the growth. Long run relation of the variables is ensured by the bound test and ECM-1 is significantly negative and indicating that adjustment is corrected by 145%. Hypotheses testing ensure except export other variables are short-run determinants of growth.